Designing a Web-Based Student Attendance System for Madrasah Ibtidaiyah Al Hikmah Debong - Moh. Rival Ghulam Khadiri; Wahyu Krishantoro (Yayasan Kita Menulis, 2025)
Monitoring student attendance at school is a shared responsibility between the school and parents or guardians. However, the manual attendance system currently in use often leads to issues, such as students being absent without permission and going unnoticed. For instance, a student may inform their parents that they are going to school but fail to attend classes. This situation raises serious concerns for both the school and parents, as it impacts student discipline and supervision. To address these issues, a web-based student attendance system is required to monitor attendance more effectively and in real time. This system is designed with the primary goal of enhancing the efficiency of attendance data management, minimizing human errors in attendance recording, and providing convenience for parents and school administrators in monitoring student attendance. This study aims to contribute to the field of education by developing a modern, efficient, and integrated attendance tracking technology. The proposed web-based attendance system not only automatically records student attendance but also generates accurate attendance reports that can be accessed anytime by relevant stakeholders. Therefore, this system is expected to improve transparency, effectiveness, and accountability in supervising student attendance at Madrasah Ibtidaiyah Al Hikmah Debong.